A bias away from Th2 in amniotic fluid is involved in preeclampsia. (August 2022) - Rong, Xiaoying; Zhang, Jie; Zhao, Yangyu; Xue, Lixiang; Guo, Xiangyang; Wang, Mingya; Xiang, Qian; Zeng, Hong
Abstract: Inflammatory cytokines contribute to the pathophysiology of preeclampsia. However, whether the imbalance of Th1/Th2 cytokines in amniotic fluid is associated with preeclampsia is not well defined. In the present study, we collected peripheral blood and amniotic fluid from normal pregnancy (n = 25) and preeclampsia (n = 22) at last trimester during cesarean section. The Th1/Th2 cytokine levels in amniotic fluid supernatant were detected by a bead-based immunoassay. The percentage of IFN-γ + CD4 + T cells, TNF-α + CD4 + T cells, IL-4 + CD4 + T cells and IL-10 + CD4 + T cells in peripheral blood was detected by flow cytometry. We found that in normal pregnancy, the IFN-γ/IL-4 and IFN-γ/IL-5 ratios were decreased in amniotic fluid supernatant compared to that in plasma, indicating a Th2 bias. However, IFN-γ/IL-4 (P = 0.014), IFN-γ/IL-5 (P = 0.005) and IFN-γ/IL-13 (P = 0.047) ratios in amniotic fluid supernatant was significantly increased in preeclampsia patients. The percentage of IFN-γ + CD4 + T cells (20.70 ± 7.61% vs 16.55 ± 4.96%, P = 0.041) and TNF-α + CD4 + T cells (31.78 ± 10.66% vs 19.47 ± 13.54%, P = 0.048) was significantly elevated in preeclampsia compared to normal pregnancy. Our finding demonstrates that a shift away from Th2 bias in amniotic fluid and circulating CD4 + T cells is involved in the pathogenesis of preeclampsia. This study suggests restoring the Th2 bias in amniotic fluid might be a therapeutic target of preeclampsia. Highlights: Cytokines in amniotic fluid supernatant exhibited a Th2 bias. A shift away from Th2 bias in amniotic fluid in preeclampsia. Circulating CD4 + T cells exhibit a Th1 bias in preeclampsia.